2016
DOI: 10.1159/000447323
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Combination Therapeutics for More Complete Repair of Volumetric Muscle Loss Injuries: The Role of Exogenous Growth Factors and/or Progenitor Cells in Implantable Skeletal Muscle Tissue Engineering Technologies

Abstract: Despite the robust regenerative capacity of skeletal muscle, there are a variety of congenital and acquired conditions in which the volume of skeletal muscle loss results in major permanent functional and cosmetic deficits. These latter injuries are referred to as volumetric muscle loss (VML) injuries or VML-like conditions, and they are characterized by the simultaneous absence of multiple tissue components (i.e., nerves, vessels, muscles, satellite cells, and matrix). There are currently no effective treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 110 publications
(111 reference statements)
0
28
0
Order By: Relevance
“…HGF fibrin microthreads resulted in a significantly higher recovered force production than injuries that received no treatment or treatment with a fibrin hydrogel alone. This work has been recently acknowledged as the only study of growth factor-based repair that evaluated functional recovery in an appropriate VML injury model [191]. Histological analysis showed myofibers adjacent to implanted EDC crosslinked microthreads, indicating that the aligned microthread architecture likely guides myofiber ingrowth and alignment [187].…”
Section: Growth Factors and Cytokinesmentioning
confidence: 97%
“…HGF fibrin microthreads resulted in a significantly higher recovered force production than injuries that received no treatment or treatment with a fibrin hydrogel alone. This work has been recently acknowledged as the only study of growth factor-based repair that evaluated functional recovery in an appropriate VML injury model [191]. Histological analysis showed myofibers adjacent to implanted EDC crosslinked microthreads, indicating that the aligned microthread architecture likely guides myofiber ingrowth and alignment [187].…”
Section: Growth Factors and Cytokinesmentioning
confidence: 97%
“…Current treatments for VML focus on ful lling the wound with acellular biomaterial with or without combination with a cellular component that promotes muscle regeneration [24]. Cells currently used for VML treatments are mainly myoblasts or other myogenic stem/progenitor cells [25,26]. In this study, we demonstrated that a nonmyogenic progenitor-FAP, when induced to BAT differentiation, can be used in treating VML.…”
Section: Discussionmentioning
confidence: 77%
“…Intrinsic potential for functional rearrangement and healing is low in human muscle tissue, further diminishing with the advancement of biological age (Grasman et al, 2015;Passipieri and Christ, 2016). Without effective therapeutic management, severe and extensive tissue structural bias (e.g., volumetric muscle loss) is often predictive of poor clinical outcome, as spontaneous optimal healing is hindered or negated, which results in diminished contractility associated with fibrotic tissue formation (Montarras et al, 2005;Ciciliot and Schiaffino, 2010;Grogan et al, 2011;Sicari et al, 2014;Duffy et al, 2016).…”
Section: Phenotypic Stability Chondrogenic Potential and Biomechanicsmentioning
confidence: 99%